(untitled) (The International Journal for Scientific Research, 2025)
Recurrent pneumothorax, which frequently results from underlying bullous disease, infections, or other lung pathology, can present serious diagnostic and treatment issues. We report the case of a 38-year-old woman with recurrent right-sided pneumothorax. Following VATS bullectomy a pulmonary meningothelial-like nodule (PMLN) was discovered in the resected specimen. Progesterone receptor (PR) positivity and patchy CD56 staining were among the immunohistochemistry (IHC) results; HMB45, MNF, and oestrogen receptor (ER) were negative. Our case emphasises the value of thorough pathological examination in determining uncommon reasons for recurrent pneumothorax and the therapeutic ramifications of such.